A contribution to the in-orbit validation of a radiation-hardened communication platform to be used in small satellites - Luza, Lucas Matana (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Elétrica, Florianópolis, 2019.